Utilizing qualitative meta-analysis and meta-synthesis towards emergent trends in supersonic transport aircraft - Bruner, Timothy Samuel (My University, 2025)
There is real potential for a revival of supersonic air travel, with multiple companies developing new aircraft designs that take advantage of new design concepts, philosophies, and approaches to making these aircraft practical and profitable. As this push to return supersonic aircraft to the skies presses forward, there are questions regarding how these aircraft will operate, where they will operate, and how they will integrate into the airspace above the United States. There is a need to explore the contributing factors that will influence how and to what extent these aircraft will enter into the National Airspace System (NAS) and to what extent. This study employs a combination of a qualitative meta-analysis and a meta-synthesis to identify key themes in the literature surrounding critical influencing factors for the reintroduction of supersonic aircraft into the NAS. This study explores routine supersonic flight's regulatory, technical, societal, and economic components to identify themes and trends that provide insight into how and where the industry will evolve. These theories can be used to understand challenges and other factors hindering or aiding in reintroducing these aircraft into the NAS. The theories developed from this study highlight important factors that may influence the future of supersonic air travel. They identify regulatory hurdles, technological innovations, societal impacts, environmental concerns, and economic issues. The findings from this study are intended to offer insight and guidance into significant factors affecting the future of supersonic air transportation, offering potential avenues for solutions to new and long-standing challenges alike.
Keywords: Supersonic; Aircraft; Transport; Transportation; Trends; Qualitative meta-analysis